Gender and Social Connections as Determinants of Hypertension: A Systematic Review of Longitudinal Studies - Annalijn I. Conklin; Peter N. Guo (Reviews in Cardiovascular Medicine)
Background: Social connections impact cardiovascular diseases (CVD) morbidity and mortality, but their role in hypertension, as a CVD risk factor, and their gender inequities is less understood. This review aimed to examine the longitudinal evidence on the impact of changes in social connections on risk of hypertension among aging adults, with a specific focus on gender. Methods: A systematic search of peer-reviewed literature in Medline, Embase, Scopus, and CINAHL conducted until 10 June 2024. Prospective studies evaluating the effect of changes in living arrangement, marital status, social network, or social participation on changes in blood pressure or incident hypertension among adults aged 45 and above were included. Results: We found 20,026 records (13,381 duplicates), resulting in 6645 eligible titles/abstracts for screening and 29 texts read in full. Only six studies from three countries met inclusion criteria, with four focused on marital transitions and two on changes in living arrangement. Overall, loss of close social connections had mixed effects on changes in blood pressure or risk of hypertension. More consistent adverse CVD outcomes were observed across studies for aging adults who entered marriage or became co-living (gain of close social connections). Similarly, persistent lack of close social connections appeared to result in greater increases in blood pressure or higher risk of hypertension. Two included studies were of high quality and the rest were medium quality. Excluded studies assessing change in either CVD risk or social tie transitions were also described (n = 9). Conclusions: There is a surprising paucity of prospective evidence on social relationships as determinants of CVD risk in the aging population, despite ample research on social factors correlated with health. Limited research suggests that both gains and losses of close social connections as well as persistent lack of close social connections may alter CVD risk, but effects are specific to single-sex samples. Research and policy should prioritize causally robust high-quality studies to unravel social determinants of CVD risk as actionable evidence to inform social prescribing in CVD prevention and healthy aging strategies is still tenuous. The PROSPERO Registration: CRD42022373196, https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=373196.